The use of Information and Communication technology when completing instrumental activities of daily living. (October 2016) - Melrose, Rebecca J.; Brommelhoff, Jessica A.; Narvaez, Theresa; Natta, Laura; Riskin-Jones, Hannah H.; Sakhai, Sherwin; Wong, Lawrence; Curtis, Stacey; Horning, Sheena M.
Abstract: Purpose of the study: An important aspect of cognitive assessment is inquiry of the patient's ability to manage instrumental activities of daily living (IADLs), including finances, medication, and transportation. Information and Communication technology (ICT, e.g. smartphones, computers) has become increasingly prevalent in American culture. We aimed to characterize what IADLs were being completed with ICT, and what factors predict ICT use to manage IADLs. Design and methods: We administered a self-report survey to 505 Veterans seeking care at the VA Greater Los Angeles Healthcare System. Results: Seventy percent reported regular ICT use. Of ICT users, 76% reported use for finances, 86% for shopping, 72% for health management, 75% for transportation, and 97% for communication. Logistic regression was used to identify predictors of high ICT use. Longer duration of computer use was significant in all models. Younger age, higher education, and better self-reported memory were associated with greater use for a subset of IADLs. Veterans with more health problems were more likely to use ICT to manage their healthcare. Implications: These findings suggest that Veterans are using ICT to support IADLs. It appears appropriate for clinicians to incorporate questions about ICT use into IADLs assessment, which may assist in detecting subtle changes to day to day functioning and improve the accurate diagnosis of cognitive disorders. Highlights: Veterans who use ICT manage at least one IADL with this technology. Longer duration of computer use predicts using ICT to manage all IADLs. Younger age and better memory predict using ICT for most IADLs. Patients with worse health use ICT to manage their medical care.